SOCIAL EXCLUSION AND ACCOUNTANT - Wong Torres, Zelma (2010)
In this article what you want to show the jurisdiction of the CPA and its social responsibility face to the social exclusion, which should trasmit the essence of their knowledge based on the story that is the past face to the future the future which is the virtual information and to talk about poverty to be submerged in these two comparisons, not to shirk their responsibility as it shall from many year ago and we must move to the story that reflects how we have been overcoming hurdles today.